Telmisartan Improves Insulin Resistance of Skeletal Muscle Through Peroxisome Proliferator–Activated Receptor-δ Activation - Li, Li; Luo, Zhidan; Yu, Hao; Feng, Xiaoli; Wang, Peijian; Chen, Jian; Pu, Yunfei; Zhao, Yu; He, Hongbo; Zhong, Jian; Liu, Daoyan; Zhu, Zhiming (Diabetes (New York, N.Y.), 2013)
The mechanisms of the improvement of glucose homeostasis through angiotensin receptor blockers are not fully elucidated in hypertensive patients. We investigated the effects of telmisartan on insulin signaling and glucose uptake in cultured myotubes and skeletal muscle from wild-type and muscle-specific peroxisome proliferator–activated receptor (PPAR) δ knockout (MCK-PPARδ−/−) mice. Telmisartan increased PPARδ expression and activated PPARδ transcriptional activity in cultured C2C12 myotubes. In palmitate-induced insulin-resistant C2C12 myotubes, telmisartan enhanced insulin-stimulated Akt and Akt substrate of 160 kDa (AS160) phosphorylation as well as Glut4 translocation to the plasma membrane. These effects were inhibited by antagonizing PPARδ or phosphatidylinositol-3 kinase, but not by PPARγ and PPARα inhibition. Palmitate reducing the insulin-stimulated glucose uptake in C2C12 myotubes could be restored by telmisartan. In vivo experiments showed that telmisartan treatment reversed high-fat diet–induced insulin resistance and glucose intolerance in wild-type mice but not in MCK-PPARδ−/− mice. The protein levels of PPARδ, phospho-Akt, phospho-AS160, and Glut4 translocation to the plasma membrane in the skeletal muscle on insulin stimulation were reduced by high-fat diet and were restored by telmisartan administration in wild-type mice. These effects were absent in MCK-PPARδ−/− mice. These findings implicate PPARδ as a potential therapeutic target in the treatment of hypertensive subjects with insulin resistance.